Gastrointestinal Stromal Tumors : Bench to Bedside - Scoggins, Charles R.; Raut, Chandrajit P.; Mullen, John T. (Springer International Publishing : Imprint: Springer, 2017)
This textbook provides a comprehensive, state of the art review of this field, and will serve as a valuable resource for clinicians, surgeons and researchers with an interest in GIST. The book reviews new data about risk factors for the disease, profiles the new staging system for GIST, highlights our current understanding of genetic mutations that lead to GIST, and provides new perspectives about imaging of GIST tumors. For localized disease, a greater appreciation of organ-sparing approaches and the importance of preservation of gastrointestinal function is discussed in detail, and advances in surgical techniques are highlighted, including minimally invasive surgery. For metastatic disease, the molecular biology of GIST is reviewed in a detailed and understandable manner, including the data that has fostered novel targeted approaches that have revolutionized management. Several landmark trials have been published in the last few years and are placed in context with respect to current management. Integration of surgery and systemic therapy through consolidative approaches has yielded provocative data that promises to further advance the field, and major advances in this domain are also discussed. Gastrointestinal Stromal Tumors: Bench to Bedside will serve as a very useful resource for physicians and researchers dealing with, and interested in, this challenging malignancy. It provides a concise yet comprehensive summary of the current status of the field that will help guide patient management and stimulate investigative efforts. All chapters are written by experts in their fields and include the most up to date scientific and clinical information.
Keywords: Medicine.; Gastroenterology.; Surgery.; Surgical oncology.; elektronické knihy; electronic books